Cultural Entrepreneurs and the Dynamics of Cultural Exchange in Transnational Spaces: A Study of the Adire Guilds of Abeokuta, Nigeria - Esuga, Folusho Toyin; Nnabuenyi, Uju M (African Journal of Stability and Development (AJSD), 2025)
This study examines the activities of cultural entrepreneurs in the craft textile industry and their impact on transnational cultural exchange, using the case of the Adire guilds in Abeokuta, Nigeria. Through a mini-ethnographic approach (12 in-depth interviews, participant observation, and the review of extant literature), the research investigates how Adire guild members translate their cultural heritage and craft skills into entrepreneurial capital, utilising flows of ideas, materials, and markets despite structural constraints found in the globalised cultural-economic arenas. The theoretical bedrock adopted is Bourdieu’s (1986) concept of cultural capital and Schumpeterian entrepreneurship theory (Schumpeter, 1934), both of which emphasise that cultural entrepreneurs not only produce goods but also craft narratives, identities and networks that enhance their value. The findings reveal: (i) craft heritage is actively commodified and repackaged for transnational markets; (ii) transnational exchange is bidirectional- raw-material imports, design inspirations from diasporas, as well as exports of finished textiles and brand narratives; (iii) institutional and market constraints in the forms of competition from low-cost imports, weak intellectual-property regimes, and fragmented value chains impact how cultural entrepreneurship plays out. This paper contributes to existing research works on transnational and development studies by shedding more light on micro-level actors’ engagement in global cultural flows and offers policy implications for enhancing the craft-industry nexus in development strategies.